A cross-sectional study on the cardiovascular risk factors among residents aged 30 years and above at Rumah Jana and Rumah Runggai in Julau district from 4 September 2000 to 22 October 2000 - Ng Teck, Han; Valarmathi, a/p Masilamani; Dyg. Elena Maria, bt Abg. Draup; Suana, bt Mohd Kushairi; Nurul Sya'adah, bt Haji Hassan; Chen Chee, Kean; Fam Tem, Lom; Lim Thien, Thien; Kong Chee, Kwan; Normi, bt Suut; Siti Nor, bt Mat (Universiti Malaysia Sarawak, (UNIMAS), 2000)
A cross-sectional study on the cardiovascular risk factors was carried out among residents aged 30 and above at Rumah Jana and Rumah Runggai, Julau from September to October 2000 by fourth year medical students from Universiti Malaysia Sarawak. The cardiovascular risk factors studied were hypertension, smoking, hypercholesterolaemia, (high fasting blood cholesterol), diabetes mellitus (abnormal fasting blood glucose) and overweight. A total of 155 respondents were universally selected for the questionnaire interview and measurements of blood pressure, body mass index, fasting blood glucose and fasting total blood cholesterol. The prevalence of hypertension was found to be 37.4 %, prevalence of smoking was 21.3 %, prevalence of high fasting total blood cholesterol was 17.4 %, prevalence of abnormal fasting blood glucose was 4.5 % and the highest prevalence was of overweight which was found to be 38.7 %. Study on the association between prevalence of cardiovascular risk factors with sociodemographic data revealed four significant associations. The significant associations were male respondents were found to have higher prevalence of smoking than female respondents, prevalence of hypertension rose with the increase in the respondents age, the prevalence of overweight was higher among the lower age group and the prevalence of overweight were higher among respondents with formal education (p<0.05). Results revealed that 74.8% of the respondents have at least 1 cardiovascular risk factor and 31.6% have 2 or more cardiovascular risk factors. A significant association was found between prevalence of overweight and the prevalence of high fasting total blood cholesterol (p<0.05). Generally, the respondents have good knowledge on cardiovascular risk factors. The percentage of respondents with adequate knowledge of each of the studied cardiovascular risk factor ranged from 68.4% for hypertension to 72.9% for hypercholesterolaemia. Study on the association between knowledge on a particular cardiovascular risk factor and the prevalence of that particular cardiovascular risk factor revealed a significant association between knowledge on overweight with the prevalence of overweight (p<0.05). Results revealed that respondents have very good attitude towards cardiovascular risk factors, with the percentage of respondents with positive attitude towards each of the studied cardiovascular risk factor ranged from 80.0% to 93.5%. Significant associations were found between the attitude of respondents towards hypertension with the prevalence of hypertension and between the attitude of respondents towards smoking with the prevalence of smoking (p<0.05).